Pemberdayaan UMKM Melalui Serangkaian Program Berkelanjutan pada KWT Banguning Panguripan Desa Rejosari - Ipang Setiawan; Rendyka Ardiansyach; Altista Pradita Prismanti (Universitas Negeri Semarang, 2025)
The role of rural women's groups in the empowerment of rural communities has had a significant impact. The urgency of developing and strengthening institutions within the rural women's group is a key determinant of sustainability and success. The purpose of the dedication is to enhance motivation, enhance insight and skills, and strengthen the institutions of the newly formed women's group. The series of programmes is implemented through four stages of activities, namely the socialization of the strategic role of KWT village, the training of making donuts innovation telo, the socialisation of the importance of brands in entrepreneurial activities, and the digitization of KWT through Shopee paltform. Based on the results of the dedication of the series of programs implemented that KWT members and managers can motivate fiber mapping the correct strategy from SWOT analysis results, have new knowledge and skills about the innovation of donuts with supporting materials singkong or telo, can provide an overview related to brand registration through the official website, as well as add skills in building branding through the Shopee platform. From the various activities of dedication as the process of development and strengthening the institution of KWT Banguning Panguripan.